STANDARISASI PROGRAM ANTI-BULLYING PENCEGAHAN BULLYING PESERTA DIDIK TINGKAT SEKOLAH DASAR - Muhammad Wahyu aAi; Muhamad Sofian Hadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The study aims to develop and standardize anti-bullying programs at the elementary school level as an effort to prevent bullying incidents among students where bullying is a serious problem that can affect the physical and mental well-being of students, so it is important to create a safe and supportive educational environment and is designed to increase students' awareness of bullying behavior and impacts, and also build empathy among them. Integration of interactive methods such as musicalization and simulations to make the material more interesting and easy to understand by students and it is hoped that standardized anti-bullying programs can be applied in various other elementary schools, so that they can create a positive culture that supports the social and emotional development of students and reduce bullying incidents significantly, recommending to involve all stakeholders, including parents and communities, in efforts to prevent bullying in the educational environment.